Healthy food traditions? Nutritional quality and food composition of EU geographical indications - Gero Laurenz Höhn; Martijn Huysmans; Christophe Crombez (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2022)
The EU Green Deal aims to promote healthier diets that include more nutritious and natural foods instead of ultra-processed products. EU geographical indications (GIs) protecting traditional foods such as Roquefort cheese or Parma ham will be reinforced under the corresponding 'Farm to Fork Strategy'. Although several GI producers advertise their products as artisanal and healthy, little is known yet about whether GI foods can actually contribute to these EU policy ambitions. Therefore, we examine the nutritional quality and food composition of GIs compared to non-GIs. We base our analysis on extensive open-access data of more than 6,000 cheeses and prepared meats marketed in France including about 1,200 products regulated under 79 different GIs. We find that GIs are associated with lower overall nutritional quality based on the Nutri-Score metric, which has become one of the major candidates for harmonised nutritional labelling in the EU. Thus, future GI specifications may allow for innovative reformulations towards healthier alternatives of local food traditions. Second, our probit regressions indicate that GIs tend to be less likely to be ultra-processed and to contain food additives. However, this seems to be truer for protected designations of origin (PDOs) with typically stricter provisions than protected geographical indications (PGIs). Hence, more harmonised rules on additives could be considered to foster the natural character of GIs and consistency across PDOs and PGIs. Finally, a revised Nutri-Score may also account for the use of additives.
Keywords: O34; Q18; 330; Geographical indications; front-of-pack labelling; processed foods; Nutri-Score; NOVA; food additives